Self-serving Bias in Redistribution Choices: Accounting for Beliefs and Norms - Dianna Amasino; Davide Domenico Pace; Joel van der Weele (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
People with higher-incomes tend to support less redistribution than lower-income people. This has been attributed not only to self-interest, but also to psychological mechanisms including differing beliefs about the hard work or luck underlying inequality, differing fairness views, and differing perceptions of social norms. In this study, we directly measure each of these mechanisms and compare their mediating roles in the relationship between status and redistribution. In our experiment, participants complete real-effort tasks and then are randomly assigned a high or low pay rate per correct answer to exogenously induce (dis)advantaged status. Participants are then paired and those assigned the role of dictator decide how to divide their joint earnings. We find that advantaged dictators keep more for themselves than disadvantaged dictators and report different fairness views and beliefs about task performance, but not different beliefs about social norms. Further, only fairness views play a significant mediating role between status and allocation differences, suggesting this is the primary mechanism underlying self-serving differences in support for redistribution.
Keywords: C91; D63; D83; 330; redistribution; self-serving bias; fairness; norms; online experiments